Efecto de la herramienta colaborativa en línea mural en el trabajo en equipo con los estudiantes de la Institución Educativa Francisco Secada Vignetta, Iquitos 2024 - Cardenas Guerra, Sharp Alsi (2025)
The purpose of the research was to determine the effect of the online collaborative tool Mural on teamwork with students of the Francisco Secada Vignetta Educational Institution in the city of Iquitos in the year 2024, so the study was developed with a pre-experimental - quantitative design, where the collaborative tool Mural on teamwork was tested, working with a single group of 98 students in 5th grade of high school of the Francisco Secada Vignetta Educational Institution, the techniques used were the survey with a questionnaire as an instrument and direct observation with an observation sheet as an instrument. Among the most resultant results it can be said that on the three dimensions of the variable: communication and collaboration, coordination and organization and leadership and conflict resolution, these had a significant difference between the pre-test and post-test data, so it can be said that the online collaborative tool Mural improves teamwork with students of the Francisco Secada Vignetta Educational Institution of the city of Iquitos in the year 2024, this is confirmed by applying the Wilcoxon signed ranks test, where the significance value gave a p-value better than 0.05.